The effects of decentralization on macroeconomic instability: Does political and institutional environment matter? - Abdul Jalil, Ahmad Zafarullah (2007)
There is yet to be a consensus among economists as to the true benefits of decentralization both on the theoretical and empirical level. Nevertheless this has not stopped various countries from proceeding with the decentralizing of their economies. Indeed certain studies have shown that out of the 77 developing and transition countries with populations greater than 7 million, 63 have embarked on some form of fiscal decentralization (Helmsing, 1999; Ebel, 2000). The main objective of this paper is to shed more lights on the relationship between decentralization and macroeconomic stability. Even though there is a huge literature both theoretically and empirically on the impact of decentralization, not many of them seems to be interested on the question of the link between decentralization and macroeconomic stability. It is thus our hope through this paper tp fill this gap in the literature.